Analisis Psikologis Kontribusi Remaja di Era Revolusi Industri 4.0 : Studi Kasus di Kabupaten Ponorogo - Ika Rusdiana (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2023)
Teenagers are the millennial generation who have a fundamental role in the industrial revolution 4.0 era. Based on the 2019 infographic data regarding profiles of social media users in Indonesia, it has known that social media users are dominated by residents, with an age range of 18-34 years. This age range is a person's productive age, or the phase of adolescence and early adulthood. Then, the following questions arise, what is the condition of the youth in Ponorogo Regency? Do they understand this critical role? What are they doing in their digital lives? Are they following the spirit of the industrial revolution 4.0? Based on the results of the data analysis, it shows that the contributions of adolescents, both conceptually and contextually, were formed based on adolescents' understanding of the industrial revolution 4.0. Conceptually, the comprehension of adolescents in Ponorogo Regency about the 4.0 industrial revolution is still limited to an understanding of the opportunities and challenges they face. They do not fully understand the concept of the 4.0 era. This understanding will shape the extent of contextual contributions of youth in the 4.0 era. The role of youth in Ponorogo Regency is still low, only reaching 34.5%. However, their contributions are quite diverse, starting from the fields of business, education, and social activities. Cognitively, the contribution of adolescents, both conceptually and contextually, is formed through a cognitive process that includes remembering, understanding, applying, analyzing, evaluating, and creating. From this process, the youth of Ponorogo Regency is still at the applying stage, namely how teenagers use a procedure to solve a problem that is happening or in doing a given task.